Simulation and experimental study of cavitation region caused by longitudinal and transverse vibration of casting ultrasonic radiator. Issue 5 (15th January 2015) - Li, X Q; Li, R Q; Dong, F; Chen, P H; Jiang, R P
Abstract: The dynamic simulation of casting ultrasonic vibration system were studied based on dynamic characteristics of the system and numerical simulation of ultrasonic sound pressure field under different vibration depths in water was performed. According to the simulation results, the cavitation region was estimated, and the experiment of cavitation erosion of aluminum foil in water and amplitude test were done to verify simulation results. The results showed that the longitudinal vibration at the end of face was the major vibration of ultrasonic radiation, while there was a strong vibration on cylindrical surface. Results of amplitude test are consistent with simulation results. Cavitation region caused by ultrasonic vibration mainly below the end face of radiation. The scope and intensity of cavitation were inversely related to the distance from the end face of radiation. With the vibrating depth increased, some small cavitation regions were found at the side of radiation, cavitation region distributed uncontinuously below radiation. Cavitation field measurement and simulation results were basically consistent.